Effects of Telephone Counseling Intervention by Pharmacists (TelCIP) on Medication Adherence; Results of a Cluster Randomized Trial - Kooij, Marcel J.; Heerdink, Eibert R.; van Dijk, Liset; van Geffen, Erica C. G.; Belitser, Svetlana V.; Bouvy, Marcel L. (Frontiers in Pharmacology, 2016)
Objectives: To assess the effect of a pharmacist telephone counselling intervention on patients’ medication adherence. Design: Pragmatic cluster randomized controlled trial. Setting: 53 Community pharmacies in The Netherlands. Participants: Patients ≥18 years initiating treatment with antidepressants, bisphosphonates, Renin-Angiotensin System (RAS)-inhibitors or statins (lipid lowering drugs). Pharmacies in arm A provided the intervention for antidepressants and bisphosphonates and usual care for RAS-inhibitors and statins. Pharmacies in arm B provided the intervention for RAS-inhibitors and statins and usual care for antidepressants and bisphosphonates. Intervention: Intervention consisted of a telephone counselling intervention 7-21 days after the start of therapy. Counselling included assessment of practical and perceptual barriers and provision of information and motivation. Main outcome measure: Primary outcome was refill adherence measured over 1 year expressed as continuous outcome and dichotomous (refill rate≥80%). Secondary outcome was discontinuation within one year. Results: In the control arms 3,627 patients were eligible and in the intervention arms 3,094 patients. Of the latter, 1,054 patients (34%) received the intervention. Intention to treat analysis showed no difference in adherence rates between the intervention and the usual care arm (74.7%, SD 37.5 resp. 74.5%, 37.9. More patients starting with RAS-inhibitors had a refill ratio ≥80% in the intervention arm compared to usual care (81.4% versus 74.9% with odds ratio (OR) 1.43, 95%CI 1.11-1.99). Comparing patients with counselling to patients with usual care (per protocol analysis),adherence was statistically significant higher for patients starting with RAS-inhibitors, statins and bisphosphonates. Patients initiating antidepressants did not benefit from the intervention. Conclusions: Telephone counselling at start of therapy improved adherence in patients initiating RAS-inhibitors. The per protocol analysis indicated an improvement for lipid lowering drugs and bisphosphonates. No effect for on adherence in patients initiating antidepressants was found.